(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article examines symmetrical and asymmetrical structures in English and Uzbek fiction from a linguocultural perspective. The study is based on the assumption that textual form is not only an aesthetic device but also a carrier of culturally marked meanings. Symmetry is interpreted as balance, recurrence, equivalence, and compositional proportionality, whereas asymmetry is understood as deviation, rupture, incompleteness, and disproportionality. The aim of the research is to identify how these structures function in English and Uzbek fiction and how they reflect different cultural models of social relations, memory, and moral evaluation. The material includes English prose by Jane Austen and Virginia Woolf and Uzbek prose by Abdulla Qodiriy and Utkir Hoshimov. The analysis shows that symmetrical structures in both traditions often express order, ethical coherence, and semantic unity, while asymmetrical structures reveal emotional tension, historical instability, and individual subjectivity. In English fiction, symmetry is frequently associated with conversational balance and ironic framing, whereas asymmetry is linked to fragmentation of consciousness and unstable perception. In Uzbek fiction, symmetry more often reflects communal values, relational ethics, and narrative circularity, while asymmetry is connected with social rupture, moral conflict, and emotional loss. The article concludes that symmetrical and asymmetrical structures should be understood as linguoculturally significant strategies of meaning construction in fiction.